ISLAMIC BRANDING: PERTIMBANGAN RASIONAL DAN IDEOLOGIS DALAM PEMGAMBILAN KEPUTUSAN PEMBELIAN - M Nasir; Hidayah, Nur; Aishah Prasetyowati, Riris; Meilani Dewi, Roosita (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2024)
AbstractThis study aimed to analyze how political preferences and Islamic branding influence consumer purchasing decisions and to analyze consumer considerations in determining retail product purchasing decisions in Depok City. Political preferences and Islamic branding are quite important to study because both can help understand more about the values and beliefs that influence consumer behavior and political decisions, and ways to respond and adapt to these changes. This is useful in helping business actors determine targeted marketing strategies, as well as enriching the insights of researchers in developing cross-disciplinary Islamic economic studies. This study uses a quantitative method with Partial Least Square (PLS) data analysis techniques through SmartPLS 3.0 software. Primary research data were collected through a survey with a questionnaire. A sample of 100 respondents was selected using a purposive sampling technique. This study concluded that a person's political preferences can influence their purchasing decisions although the influence of Islamic branding on purchasing decisions is predicted to be stronger than the influence of political preferences. This is what distinguishes this study from others, namely seeing the influence of a person's purchasing decisions not only from economic variables, but also from political variables. In addition, this study also identified two groups of consumer behavior, namely ideological consumer behavior and rational consumer behavior, where each group has different considerations in purchasing decisions. AbstrakPenelitian ini bertujuan untuk menganalisis bagaimana preferensi politik dan Islamic branding memengaruhi keputusan pembelian konsumen, serta menganalisis pertimbangan konsumen dalam menentukan keputusan pembelian produk ritel di Kota Depok. Preferensi politik dan Islamic branding cukup penting untuk dipelajari karena keduanya bisa membantu kita memahami lebih jauh tentang nilai-nilai dan keyakinan yang memengaruhi perilaku konsumen dan keputusan politik, serta bagaimana kita merespon dan beradaptasi dengan perubahan tersebut. Hal ini sangat bermanfaat dalam membantu para pelaku usaha menentukan strategi pemasaran yang tepat sasaran, serta memperkaya wawasan para peneliti dalam mengembangkan kajian ekonomi Islam lintas disiplin. Penelitian ini menggunakan metode kuantitatif dengan teknik analisis data Partial Least Square (PLS) melalui perangkat lunak SmartPLS 3.0. Data primer penelitian dikumpulkan melalui survei dengan kuesioner. Sampel sebanyak 100 responden dipilih menggunakan teknik purposive sampling. Penelitian ini menyimpulkan bahwa preferensi politik seseorang dapat memengaruhi keputusan pembelian mereka. Meskipun pengaruh Islamic branding terhadap keputusan pembelian diprediksi lebih kuat dibandingkan pengaruh preferensi politik. Hal inilah yang membedakan penelitian ini dengan yang lain, yaitu melihat pengaruh keputusan pembelian seseorang tidak hanya dari variabel ekonomi, tapi juga dari variabel politik. Selain itu, penelitian ini juga mengidentifikasi dua kelompok perilaku konsumen, yaitu perilaku konsumen ideologis dan perilaku konsumen rasional, di mana masing-masing kelompok memiliki pertimbangan berbeda dalam keputusan pembelian.